2017
DOI: 10.1111/hsc.12427
|View full text |Cite
|
Sign up to set email alerts
|

An open trial of equine-assisted therapy for children exposed to problematic parental substance use

Abstract: Children exposed to problematic parental substance use (PPSU) often face a number of deleterious developmental outcomes, yet these children are less likely to become known to child protection and welfare services. Although there is a growing evidence base for equine-assisted therapy (EAT) as an effective treatment modality for atypically developing children and adolescents, scant research has explored the benefit of EAT for children exposed to PPSU. The current study is the first to explore the benefit of EAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Participants of these programs have reported reduced anxiety and depression symptoms [ 22 , 29 , 32 , 33 ] reduced PTSD symptoms [ 34 , 35 ], elevated self-esteem and self-awareness [ 30 ], improved communication and trust [ 31 , 34 ], and increased overall well-being [ 23 ]. However, the majority of this research has focused on children and adolescents [ 24 , 31 , 32 ] with limited peer-reviewed studies investigating the utility of equine-assisted therapy for military veterans [ 25 , 27 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants of these programs have reported reduced anxiety and depression symptoms [ 22 , 29 , 32 , 33 ] reduced PTSD symptoms [ 34 , 35 ], elevated self-esteem and self-awareness [ 30 ], improved communication and trust [ 31 , 34 ], and increased overall well-being [ 23 ]. However, the majority of this research has focused on children and adolescents [ 24 , 31 , 32 ] with limited peer-reviewed studies investigating the utility of equine-assisted therapy for military veterans [ 25 , 27 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…EAT is used in combination with psychological settings. The primary target group of this specific intervention are children and adolescents who have a holistic need for therapy [3,4]. Case studies with adults discussed in the literature are predominantly EAT for the treatment of a diagnosed disorder, whereas preventive approaches receive little attention [5].…”
Section: Equine-assisted Therapymentioning
confidence: 99%
“…Parents of children (n = 41) and school teachers (n = 31) completed the Force and Difficulty Questionnaire (SDQ) before and after the intervention. The parents reported that after the 12week EAT programme the problems with children's behaviour, emotional problems, hyperactivity and peer problems decreased, while the pro-social behaviour of the children improved (Tsantefski et al, 2017).…”
Section: Schizophreniamentioning
confidence: 99%